2003
DOI: 10.1002/cphc.200300698
|View full text |Cite
|
Sign up to set email alerts
|

Adducts of Xenon with Organic Molecules: Rotational Spectrum of Dimethyl Ether–Xe

Abstract: KEYWORDS:gas-phase reactions ¥ noble gases ¥ rotational spectroscopy ¥ van der Waals adducts ¥ xenon Considerable interest has been devoted during the last two decades to the investigation of the rather unusual ™chemical compounds∫ formed by the combination of a noble gas atom with an organic molecule.[1] Various spectroscopic methods have been used to observe these adducts in the plume following a supersonic expansion.[2] Many van der Waals adducts between a noble gas atom and a cyclic organic molecule have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…1 Coming back to the nonbonding interactions involved in the molecular complexes of DME, we can divide them in several categories. (i) van der Waals interactions characterize the adducts with rare gases, whose interaction energies are in the range 1.0−3.6 kJ/mol in going from DME−Ne 2 to DME−Ar, 3 DME−Kr, 4 and DME−Xe, 5,6 according to a linear dependence with the square of the rare gas atom polarizability. (ii) Weak hydrogen bonds of the type C−H•••O or C−H•••F (2 to 3 kJ/mol for each of them) link the subunits in the dimer of DME or in its adducts with hydrogen-containing freons.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Coming back to the nonbonding interactions involved in the molecular complexes of DME, we can divide them in several categories. (i) van der Waals interactions characterize the adducts with rare gases, whose interaction energies are in the range 1.0−3.6 kJ/mol in going from DME−Ne 2 to DME−Ar, 3 DME−Kr, 4 and DME−Xe, 5,6 according to a linear dependence with the square of the rare gas atom polarizability. (ii) Weak hydrogen bonds of the type C−H•••O or C−H•••F (2 to 3 kJ/mol for each of them) link the subunits in the dimer of DME or in its adducts with hydrogen-containing freons.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Coming back to the nonbonding interactions involved in the molecular complexes of DME, we can divide them in several categories. (i) van der Waals interactions characterize the adducts with rare gases, whose interaction energies are in the range 1.0–3.6 kJ/mol in going from DME–Ne to DME–Ar, DME–Kr, and DME–Xe, , according to a linear dependence with the square of the rare gas atom polarizability. (ii) Weak hydrogen bonds of the type C–H···O or C–H···F (2 to 3 kJ/mol for each of them) link the subunits in the dimer of DME or in its adducts with hydrogen-containing freons. (iii) Conventional hydrogen bonds have been found to constitute the main linkage with the partner molecule in complexes of DME with hydrogen halides , or alcohols. In these complexes the dissociation energies have been estimated to be in the range 15–25 kJ/mol.…”
Section: Introductionmentioning
confidence: 99%
“…From these splittings, the barriers to the rotation of the rare gas around dimethyl ether were estimated to be 0.19 and 0.69 kJ mol -1 , respectively. In the case of DME-Xe, no inversion splittings have been observed 1 Sketch of DME-Kr.…”
Section: Introductionmentioning
confidence: 99%
“…16,28 Xenon has also been shown to form weakly bound complexes in solid rare gases with other compounds, such as HCl, CN, dimethyl ether, benzene, oxirane, and difluorovinylidene. [29][30][31][32][33] Theoretical studies on xenon-containing compounds have been reported over the past decade. H-Xe-R (R ¼ C 6 H 5 or other hydrocarbons) was predicted to be a stable species.…”
Section: Introductionmentioning
confidence: 99%